Slow Light Enhanced Phase Shifter Based on Low-Loss Silicon-ITO Hollow Waveguide - Swati Rajput; Vishal Kaushik; Sourabh Jain; Mukesh Kumar (IEEE Photonics Journal)
An optical phase shifter based on narrow-core hollow waveguide is proposed. The light is guided in an air core between the top and bottom reflectors made up of silicon and indium tin oxide (ITO) gratings. The proposed narrow-core hollow structure is able to guide slow light mode with a low loss of 0.2 dB/cm and a high group index of 64 in 0.8 μm thick air core. The presence of ITO enables electrically controlled phase shifting. In order to realize phase shifting, a p-i-n junction in ITO is used around the air core and in the top and bottom gratings. The geometry is optimized for enhanced interaction between the free charge carriers injected in the intrinsic region of ITO and the propagating optical mode. The proposed device shows a phase shifting of 180° for a 71-μm long device resulting from the slow-light effect.